Development of sustainable integrated biorefinery networks in pulp and paper industries - Mongkhonsiri, Ghochapon; Anantpinijwatna, Amata; Charoensuppanimit, Pongtorn; Arpornwichanop, Amornchai; Gani, Rafiqul; Assabumrungrat, Suttichai (My University, 2021)
With the objective to obtain more sustainable production processes, the biorefinery network is integrated with traditional pulp and paper industries. A systematic framework with computer-aided tools consisting of synthesis, design and innovation stages has been applied to determine the biorefinery-integrated pulping process. An integrated network of succinic acid production and black liquor gasification for dimethyl ether (DME) production linked to an existing Soda pulping process is identified as the best option for increased profit, which also reduces pollutant emissions through integration of innovative CO2 capture and utilization (CCU) steps to form the biorefinery-integrated-Soda-pulping network (BIS). This paper aims at also designing a sustainable biorefinery-integrated-Kraft-pulping network (BIK). Three integration scenarios are considered for further study: (I) the production of gasification-based dimethyl ether (DME); (II) the coproduction of DME and succinic acid (SA); and (III) the co-production of DME and SA coupled with CCU. The best scenario is found to be Scenario II, which exhibits the best economic performance with 74% increase in profit compared to the conventional process. Scenario III achieves the highest energy efficiency at 39% and improved environmental performance, a 65% reduction of CO2 emission compared to the conventional process, with only 0.7% profit reduction. The BIK option shows improved performance in terms of economic and environmental improvements compared to the BIS network, confirming that the integrated biorefinery network can transform the conventional Kraft pulping process to a more sustainable process with increased profit.
Keywords: Biorefinery network; Process synthesis and design; Pulp and paper industries; Systematic framework with computer-aided tool